2013
DOI: 10.1534/g3.113.005595
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective View of North American Potato (Solanum tuberosumL.) Breeding in the 20th and 21st Centuries

Abstract: Cultivated potato (Solanum tuberosum L.), a vegetatively propagated autotetraploid, has been bred for distinct market classes, including fresh market, pigmented, and processing varieties. Breeding efforts have relied on phenotypic selection of populations developed from intra- and intermarket class crosses and introgressions of wild and cultivated Solanum relatives. To retrospectively explore the effects of potato breeding at the genome level, we used 8303 single-nucleotide polymorphism markers to genotype a 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
164
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 180 publications
(178 citation statements)
references
References 38 publications
(43 reference statements)
13
164
0
1
Order By: Relevance
“…In this study, the Infinium SolCAP 8K was used to genotype accessions of the CCC, providing informative data with 72% of polymorphic loci. Previous studies in potato germplasm of other collections reported similar level of polymorphism using the same array: 77% [9], 74% [22], 61% [23], 67% [25], and 76% [66]. A degree of ascertainment bias could be expected when the SolCAP 8K is used to analyze populations such as the Colombian potato germplasm because it was designed based on transcriptome data and EST databases of North American cultivars [19, 21].…”
Section: Discussionmentioning
confidence: 96%
“…In this study, the Infinium SolCAP 8K was used to genotype accessions of the CCC, providing informative data with 72% of polymorphic loci. Previous studies in potato germplasm of other collections reported similar level of polymorphism using the same array: 77% [9], 74% [22], 61% [23], 67% [25], and 76% [66]. A degree of ascertainment bias could be expected when the SolCAP 8K is used to analyze populations such as the Colombian potato germplasm because it was designed based on transcriptome data and EST databases of North American cultivars [19, 21].…”
Section: Discussionmentioning
confidence: 96%
“…The SolCAP potato diversity panel consists of both diploid and tetraploid wild species, genetic stocks, and cultivated potato lines with release dates ranging from 1857 to 2011 (Hirsch et al, 2013). The panel was genotyped with an Infinium SNP array of 8303 markers (Hamilton et al, 2011; Felcher et al, 2012), and tetraploid marker dosage was determined by Hirsch et al (2013), principally by visual inspection of the cluster boundaries. Our analysis of population structure was conducted using all 221 tetraploid lines in the panel (Supplemental Table S1), while GWAS results are based on the 187 tetraploid lines with both marker and phenotypic data.…”
Section: Methodsmentioning
confidence: 99%
“…Ten to twenty five tubers were collected from each of the local varieties identified by growers, traders or marketers. Varieties were genotyped with 8303 SNPs, using the potato Illumina Infinium array developed by the SolCAP project (Hirsch et al 2013). Varieties that shared genotype calls at 99 % or more of the SNP loci were deemed identical.…”
Section: The Map Created By: Disaster Prevenɵon and Preparedness Commmentioning
confidence: 99%